PENGARUH DIAGNOSTIC CONTROL SYSTEM TERHADAP CUSTOMER-ORIENTED MEASURES MELALUI EMPLOYEE-ORIENTED MEASURES SEBAGAI VARIABEL INTERVENING - Yohanes Rudolf Benu; Saarce Elsye Hatane (Business Accounting Review, 2017)
The purpose of this study is to determine the impact of diagnostic control system on customer-oriented measures towards employee-oriented measures as an intervening variable. The population used in this study are 31 public companies which operated in Surabaya, with a sample size of 104. The analysis technique used in this study is a partial least square. The result of the study shows that the diagnostic control system has a significant positive effect on employee-oriented measures, employee-oriented measures has a significant positive effect on customer-oriented measures, and diagnostic control system has a positive significant effect on customer-oriented measures.